Optical scattering : measurement and analysis - Stover, John C. (SPIE Optical Engineering Press, 1995)
As the authoritative resource on optical scattering, this book was developed from many years of teaching light-scatter measurement and analysis courses to optical engineers. Dr. Stover covers scattering beginning with its basics and covering surface roughness calculations, measurements, instrumentation, predictions, specifications, and industrial applications. Also included are appendices that review the basics of wave propagation and Kirchhoff diffraction. Whether you're an optical engineer currently investigating roughness-induced haze in the semiconductor industry, or just entering the field of scatter metrology, this text will be invaluable.
Keywords: Light -- Scattering.; elektronické knihy; electronic books